Evaluating the effect of Neoadjuvant chemotherapy for esophageal Cancer using the RECIST system with shorter-axis measurements: a retrospective multicenter study - Yusuke Taniyama; Kentaro Murakami; Naoya Yoshida; Kozue Takahashi; Hisahiro Matsubara; Hideo Baba; Takashi Kamei (BMC Cancer, 2021)
Abstract Background Evaluating the effect on primary lesions is important in determining treatment strategies for esophageal cancer. The Response Evaluation Criteria in Solid Tumors system, which employs the longest diameter for measuring tumors, is commonly used for evaluating treatment effects. However, the usefulness of these criteria in assessing primary esophageal tumors remains controversial. Thus, we evaluated this issue by measuring not only the longest diameter but also the shorter axis of the tumor. Methods We retrospectively reviewed data from 313 patients with esophageal cancer treated with neoadjuvant chemotherapy followed by esophagectomy at three major high-volume centers in Japan. All patients underwent contrast-enhanced computed tomography before and after chemotherapy. The longest and shortest tumor diameters were measured in each case. Treatment effects were adapted to the Response Evaluation Criteria in Solid Tumors system. Correlations between pathological and survival data were also analyzed. Results Inter-observer discrepancies were examined for changes in the longest diameter and shorter axis of the tumor (the intraclass correlation coefficients were 0.550 and 0.624, respectively). The shorter axis was correlated with the pathological response in the multivariate analysis (p < 0.001). The shorter axis was significantly associated with overall survival and disease-free survival (both p < 0.001), whereas this association was not observed for the longest tumor diameter. Conclusions This multicenter study demonstrated that the Response Evaluation Criteria in Solid Tumors system is useful for predicting pathological response and survival by incorporating the shorter axis of the primary esophageal tumor.